Interspecies Genomic Variation and Transcriptional Activeness of Secondary Metabolism-Related Genes in Aspergillus Section Fumigati - Takahashi, Hiroki; Umemura, Maiko; Ninomiya, Akihiro; Kusuya, Yoko; Shimizu, Masaaki; Urayama, Syun-ichi; Watanabe, Akira; Kamei, Katsuhiko; Yaguchi, Takashi; Hagiwara, Daisuke (Frontiers in Fungal Biology, 2021)
Filamentous fungi produce various bioactive compounds that are biosynthesized by sets of proteins encoded in biosynthesis gene clusters (BGCs). For an unknown reason, many BGCs are transcriptionally silent in laboratory conditions, which has hampered the discovery of novel fungal compounds. The transcriptional reactiveness of fungal secondary metabolism is not fully understood. To address this issue, we conducted comparative genomic and transcriptomic analyses of nine closely-related species of Aspergillus section Fumigati (A. fumigatus, A. fumigatiaffinis, A. novofumigatus, A. thermomutatus, A. viridinutans, A. pseudoviridinutans, A. lentulus, A. udagawae, and Neosartorya fischeri). For this purpose, we newly sequenced genomes of A. viridinutans and A. pseudoviridinutans, and reassembled and reannotated the previously released genomes of A. lentulus and A. udagawae. Between 34 and 84 secondary metabolite (SM) backbone genes were identified in the genomes of these nine respective species, with 8.7%–51.2% being unique to the species. A total of 247 SM backbone gene types were identified in the nine fungi. Ten BGCs are shared by all nine species. Transcriptomic analysis using A. fumigatus, A. lentulus, A. udagawae, A. viridinutans, and N. fischeri was conducted to compare expression levels of all SM backbone genes in four different culture conditions; 32%–83% of SM backbone genes in these species were not expressed in the conditions tested, which confirmed that fungal SM genes are mostly silent. The species-unique SM genes of the five species were expressed with lower frequency (18.8% in total) than the SM genes that are conserved in all five species (56%). These results suggest that the expression tendency of BGCs is correlated with their pan-genomic distribution pattern. Our findings increase understanding of the evolutionary processes associated with the regulation of fungal secondary metabolism.